KARAKTERISTIK KERJA PARALEL GENERATOR INDUKSI DENGAN GENERATOR SINKRON YANG TERHUBUNG JURUSAN TEKNIK ELEKTRO DAN FAKULTAS TEKNIK UNIVERSITAS GADJAH MADA DENGAN GRID - , MUHRILLAHIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Distributed Generation (DG) is anysmall-scalepowergenerationtechnologythat provides electric power at a site closer to customers than central station generation. Adistributionpowerunitcanbeconnecteddirectlytotheconsumers or to a utilityâs transmission or distribution system. Induction generator and synchronous generator are familiar power converter which is used to technology of DG. This research will gives knowledge about characteristics of parallel operated synchronous generator and induction generator which are connected to grid. The research object is gotten from an IEEE jounal. Simulink model is simulated to get the objects of research. This research show that synchronous generator which is operated over-excitation will transfer the reactive power to MISG. Loss Of Grid (LOG) condition will affects system voltage and current of synchronous generator. The maximum excitation current of synchronous generator to prevent bad effect of LOG is 2,3 pu. At the maximum performance of generators, they can produce 6,8 kW and 8,74 kVAr. When LOG is held, the safe load value is about 69% to 100% full load.